PENERAPAN STRATEGI PEMBELAJARAN BERDIFERENSIASI DALAM KELAS HETEROGEN UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SMAS ITP TARJUN - Alfayed, Dody; Suriansyah, Ahmad; Purwanti, Ratna (Jurnal Manajemen Pendidikan, 2025)
There are many learning strategies in the current era. The right strategy will also provide good results. Currently, the learning strategy that is often applied is differentiation. Differentiated learning strategies generally adjust the content, process, and learning products according to the readiness, interests, and learning profiles of students. The purpose of this study was to examine the application of differentiated learning strategies in heterogeneous classes at SMAS ITP Tarjun. Subjects were selected purposively, including principals, teachers, and students. Data analysis was carried out thematically to reveal patterns of strategies, challenges, and their impact on the quality of learning. The results of the study showed that teachers implemented learning differentiation according to student needs with the support of the principal's transformational leadership through routine coaching and developing a reflective culture of teachers to build the spirit of the independent curriculum. Despite the obstacles, teachers continued to try to develop strategies to increase student motivation and create an inclusive and quality learning environment.